2013
DOI: 10.1111/febs.12417
|View full text |Cite
|
Sign up to set email alerts
|

miR‐144 downregulation increases bladder cancer cell proliferation by targeting EZH2 and regulating Wnt signaling

Abstract: microRNAs (miRNAs) have been proposed to be key regulators of diverse biological processes such as transcriptional regulation, cell growth and tumorigenesis. Wnt signaling plays an important role in the regulation of tumorigenesis and cancer progression. However, little is known about whether miR‐144 regulates bladder cancer cell proliferation by controlling Wnt signaling. In this study, we found that the miR‐144 expression level is significantly decreased in bladder cancer cell lines as well as in clinical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 30 publications
(43 reference statements)
5
108
0
1
Order By: Relevance
“…Based upon the abundant data accumulated during the past two decades, scientists began to argue for use of miRNAs as novel therapeutic targets for various malignancies (33). MiR-144 has been implicated in both oncogenic and tumorsuppressive roles in different tumors, but its role in DLBCL is not yet clarified (34)(35)(36). Although research on the true biologic relevance of miR-144 in cancer is still in its infancy, in this study we focused on the expression and function of miR-144 in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the abundant data accumulated during the past two decades, scientists began to argue for use of miRNAs as novel therapeutic targets for various malignancies (33). MiR-144 has been implicated in both oncogenic and tumorsuppressive roles in different tumors, but its role in DLBCL is not yet clarified (34)(35)(36). Although research on the true biologic relevance of miR-144 in cancer is still in its infancy, in this study we focused on the expression and function of miR-144 in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-144 has recently been shown to be downregulated in bladder cancer, which leads to loss of inhibition of zeste homolog 2 and subsequent activation of Wnt/β-catenin signaling with ensuing cellular proliferation. 45 Xie et al 46 showed that miR-497 is underexpressed in hepatocellular carcinoma and that this miRNA is a negative regulator of checkpoint kinase 1, which functions in cell cycle arrest after DNA damage. The roles of these tumor suppressor miRNAs have not yet been explored in the biology of adipocytic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…miR-144 has been revealed to be involved in multiple types of human malignancy (4,5). In addition, miR-144 was reported to act as a tumor suppressor in certain types of cancer, including bladder (4), non-small cell lung (6) and colorectal (7) cancer.…”
Section: Introductionmentioning
confidence: 99%